A 77 GHz Direction of Arrival Detector System with SiGe Integrated Six-Port Receiver - Vinci, Gabor; Lämmle, Benjamin; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (Radio-Wireless Symposium, 2012)
In this publication the design of a 77 GHz Direction-Of-Arrival (DOA) detector system with an Integrated SiGe six-port receiver and a passive microstrip antenna network is presented. The introduction of the six-port receiver for industrial sensors and automotive radar applications has opened a whole new set of possibilities and implementations. A typical problem though of Millimeter-Wave (MW) integration is the interface between the on-chip circuitry and the off-chip system electronics or passives. The antenna design aspects and interconnections are presented with a layouting analysis as well as a system overview of the DOA detector for a flexible, low-complexity and low-cost solution in microstrip technology.
elib2cris::1512001600,vinci2012a
Keywords: Antenna measurements; Antennas; Automotive engineering; Detectors; Microstrip; Radar; Receivers